Relationship analysis of TNF and IL8 gene polymorphisms with clinical features of chronic obstructive pulmonary disease - G. N. Seitova; Ye. B. Bukreyeva; I. S. Kremis; V. P. Puzyryov (Бюллетень сибирской медицины)
The correlation of the 308G/A polymorphism of α TNF (tumor necrosis factor) gene and 251А/Т polymorphism of 8 IL8 (interleukin 8) gene with clinical peculiarities of the course of chronic obstructive lung disease (COLD) in Siberian Tatars and Russians has been studied. Associations of these genetic markers with quantitative indices pathogenetically significant in the COLD formation (biochemical and immunological indices of blood serum and sputum) have been analyzed.The analysis of associations of polymorphous versions of TNF and IL8 genes with biochemical and immunological indices of blood serum and sputum has revealed the presence of interethnic peculiarities in the regulation of the level of proinflammatory and protective mechanisms participating in the formation of chronic inflammation at COLD.